Construct Validity Analysis of Stellar Evolution Concept Mastery Test to Reduce Misconceptions - Permata, Hilda; Liliawati, Winny; Utama, Judhistira Aria (Proceedings International Conference on Education Innovation and Social Science, 2024)
This study aims to determine the validity of an instrument that is able to measure misconceptions and accommodate multiple intelligences. The development of the Star Evolution Concept Mastery Test instrument is an instrument containing fifteen multiple choice questions based on stellar evolution material from the beginning of the birth of a star to the death of a star. This research uses the Research & Development (R&D) method. To determine the validity of this instrument, expert judgment was carried out by two experts in their fields. Expert judgment was conducted to determine construct validity. From the results of the analysis, it was found that almost all questions were accepted and could be used after revision according to the notes from the experts. So that the instrument is considered feasible and declared valid, which means that this instrument can measure misconceptions and can be used.